Effects of specific symbiotic supplements on anthropometric measurements, glycaemic control, and lipid profiles among individuals with type 2 diabetes mellitus in two teaching hospitals in Baghdad/Iraq: a double-blinded, randomised placebo-controlled trial - Sarah Hayder Ali Zalzala; Ban Abdul-Ridha Salman Al-Hashimi; Zahraa Hayder Ali Zalzala; Khalid Saeed Fahad (BMC Nutrition)
Abstract Background Experimental and clinical studies have suggested that symbiotics might effectively manage type 2 diabetes mellitus (T2DM) by modulating the intestinal microbiota. However, these studies’ limited sources, small sample sizes, and varied study designs have led to inconsistent outcomes regarding glycaemic control. This study aimed to investigate the effects of symbiotics on the anthropometric measures, glycaemic control, and lipid profiles of patients with T2DM. Methods A double-blind, placebo-controlled, parallel clinical trial was conducted at two diabetes outpatient clinics. The main researcher and participants were blinded to the capsule content throughout the study. Sixty-six patients with T2DM aged 30–75 years were randomly allocated, using even and odd numbers, into two equal groups. These groups received either symbiotic capsules containing 200 million colony-forming units plus fructo-oligosaccharide or a placebo for 12 weeks. The primary objective was a decrement in glycated haemoglobin [HbA1c]. The patients’ anthropometric measures, fasting blood sugar, high-density lipoprotein [HDL], low-density lipoprotein [LDL], total serum cholesterol and serum triglyceride levels were also assessed at baseline and after 12 weeks of intervention. Non-parametric tests were used for statistical analyses. Results Within-group analysis revealed significant decreases in body mass index (BMI) and waist circumference (P = 0.005 and 0.023, respectively) and a significant increase in HDL levels in the symbiotic group (P = 0.04). HbA1c levels significantly increased in the placebo group (P = 0.016) but were not significantly reduced in the symbiotic group. The between-group analysis revealed significantly lower fasting blood sugar (FBS) levels in the symbiotic group, and higher in the placebo group (P = 0.02). No significant changes existed in total serum cholesterol, LDL, and triglyceride levels in either the symbiotic or placebo group. Conclusions Symbiotics improve BMI, waist circumference, HDL, and FBS levels and prevent the worsening of HbA1c levels in patients with T2DM. Our preliminary results indicate the potential benefits of symbiotics in patients with T2DM, which may lead to better diabetes control. However, this evidence requires further assessment in larger trials. Trial registration The trial was registered retrospectively at the International Standard Registered Clinical/Social Study Number Registry (ISRCTN34652973) on 05/01/2024.